The Therapeutic Potential of miR-7 in Cancers - Li, Miao; Pan, Meng; You, Chengzhong; Dou, Jun (Mini Reviews in Medicinal Chemistry, 2019)
MiRNAs play an important role in cancers. As a potent tumor suppressor, miRNA-7(miR-7) has been demonstrated to inhibit the diverse fundamental biological processes in multiple cancer types including initiation, growth and metastasis by targeting a number of molecules and signaling pathways. This current review summarizes and discusses the relationship between miR-7 and cancers and the therapeutic potential of miR-7 in cancers. It may provide new integrative understanding for future study on the role of miR-7 in cancers.
Keywords: cancer cell signaling